The liverwort family Lejeuneaceae (Marchantiophyta) of Mount Lubuk Raya, North Sumatra, Indonesia - etti sartina siregar; NURSAHARA PASARIBU; KHAIRANI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Siregar ES, Pasaribu N, Khairani. 2020. The liverwort family Lejeuneaceae (Marchantiophyta) of Mount Lubuk Raya, North Sumatra, Indonesia. Biodiversitas 21: 2767-2776. Lejeuneaceae is the largest family in the liverworts. Information on the species of Lejeuneaceae in North Sumatra is still less reported, especially in Mount Lubuk Raya has never been reported. Therefore, the aim of this study is to explore the diversity of Lejeuneaceae in Mount Lubuk Raya, North Sumatra. The study was done using survey method by exploring along the hiking tracks on the study site. All the samples found were collected and then identified in the laboratory-based on morphological characters used the existing literature of Lejeuneaceae. Thirty-seven species of Lejeuneaceae, belonging to 18 genera were identified from Mount Lubuk Raya. Eight species are proposed as new reported for Sumatra: Ceratolejeunea belangeriana, Colura vitiensis, Lejeunea curviloba, Lejeunea dipterota, Lepidolejeunea bidentula, Leptolejeunea maculata, Schiffneriolejeunea pulopenangensis, Spruceanthus planiusculus. Identification key of species and pictures of species newly recorded is provided in this paper.